VALIDATION OF E-BOOK LEARNING MEDIA BASED ON SEXUAL VIOLENCE EDUCATION ON STUDENTS' UNDERSTANDING OF SEXUAL VIOLENCE IN THE REPRODUCTIVE SYSTEM - Fitria Eka Wulandari; Atira Diyah Pangesti; Noly Shofiyah; Hidayatulloh (Academic Journal Research, 2026)
Objective: This research was conducted to develop and test the feasibility of learning media for Sexual Violence Education-Based Reproductive System E-Book. Method: Therefore, this research was carried out using research and development methods to produce interesting, valid, and appropriate media, namely an e-book on reproductive systems based on sexual violence education which aims to improve the understanding of sexual violence in junior high school students. This learning media is validated by three validators. Results: The results show that this learning media is very feasible and valid to use with a feasibility percentage of 100% for the material score and 98.6% for the e-book visual media score. Suggestions and inputs from the three validators are the basis for improving this learning media. Novelty: Based on initial observations, problems were encountered that education about sexual violence was only an interlude during the learning time, not packaged directly in the learning process as outlined in the textbook or written in the learning steps.